Directory of world cinema. - Hortelano, Lorenzo J. Torres (Directory of World Cinema Series., 2011)
Part of the "Directory of World Cinema" series, this title includes contributions from some of the leading academics in the field. It features film recommendations from a range of genres for those interested in watching more German cinema. It includes 50 full colour illustrations. It also features comprehensive filmography as an index. Spanish Cinema is one of the most diverse and interesting to international level; but lacks communication platforms and detailed analysis. This new volume of the "Directory of World Cinema" addresses the issue. It focuses on the main corpus o.